Home-Market and Cost Effects of International Product-Quality Allocation - Kiyoshi Matsubara (European Regional Science Association (ERSA), 2012)
This paper analyzes the behavior of firm(s) serving its products to two countries having different consumers in terms of their valuation of product quality. The home-market of firm(s) is a developed country with small population but high valuation of product quality, while the foreign is a developing country with large population but low valuation of product quality. The main focus of this paper is on how the product-quality choice in different markets is related with the cost structure of the firm and market conditions. In case when the home and foreign markets are equally important for firms, firms must choose globally optimal resource allocations. Therefore, the setting in this paper is suitable for analyzing EU or Japanese firms operating in both their home countries and emerging economies. About the cost structure, costs depending on quantity and quality(named gproduction costsh) and those depending only on quality (named gR&D costsh) are discussed. With production and R&D costs, three types of costs are examined. Type 1 costs have no R&D costs. Type 2 costs have both, and R&D costs are convex in product quality. Type 3 costs have both and both costs are convex in product quality. In each setting, this paper examines which of the following two strategies gives higher profits to firm(s). One is gcommon quality,h supplying the common-quality products to the both markets. The other is gdifferent quality,h supplying the different quality products to the two markets. This paper examines the effects of production and R&D costs on the product quality in the two monopoly markets separately, and then discusses two general cases: (1) two firms from different developed countries enter the developing-country market and (2) downward-sloping demand curve assuming a distribution of consumers in each country. This paper shows that if the effects of production costs or the home-market dominate, providing different levels of product quality is optimal and that if the effects of R&D costs or the developing-market dominate, providing the common level of quality is optimal. These results also depend on the types of costs and the market structure of the developing country.
Keywords: F12; F23; O33; 330; Product Quality; Different Markets; Costs of Quality